2019
DOI: 10.3389/fcimb.2019.00214
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Proteolysis in Vibrio cholerae Allowing Rapid Adaptation to Stress Conditions

Abstract: The lifecycle of the causative agent of the severe secretory diarrheal disease cholera, Vibrio cholerae , is characterized by the transition between two dissimilar habitats, i.e., as a natural inhabitant of aquatic ecosystems and as a pathogen in the human gastrointestinal tract. Vibrio cholerae faces diverse stressors along its lifecycle, which require effective adaptation mechanisms to facilitate the survival fitness. Not surprisingly, the pathogen's transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…By targeting transcription factors for proteolysis, bacteria can modulate their gene expression profiles in response to new environmental stimuli. Several studies have demonstrated that the avirulent phenotypes associated with protease-deficient mutants are due in large part to such aberrant gene regulation [ 41 , 42 , 43 ]. Interestingly, we found that the clpA and clpS mutant strains exhibit formidable phenotypic changes including alterations to cell size, shape and especially in clpA , a possible defect in bacterial separation during replication.…”
Section: Discussionmentioning
confidence: 99%
“…By targeting transcription factors for proteolysis, bacteria can modulate their gene expression profiles in response to new environmental stimuli. Several studies have demonstrated that the avirulent phenotypes associated with protease-deficient mutants are due in large part to such aberrant gene regulation [ 41 , 42 , 43 ]. Interestingly, we found that the clpA and clpS mutant strains exhibit formidable phenotypic changes including alterations to cell size, shape and especially in clpA , a possible defect in bacterial separation during replication.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one possibility is that stress-dependent regulation of ClpAP indirectly regulates Pchb. It has also been hypothesized that V. cholerae makes use of proteolysis machines to rapidly respond to changes in their environment; namely, the transition from the human gut to the aquatic environment after infection (43). ClpAP acting as an activator of Pchb may be a way for cells to rapidly induce expression of a locus that is not important in the human gut, but is useful for survival in its aquatic reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…DegS is a serine protease located in the periplasm of bacteria, and is an important component of the bacterial response to external pressure (Kim, 2015). The degS is now seen as an essential gene whose indispensable function is to provide active σ E activity (Alba et al, 2001; Pennetzdorfer et al, 2019). However, the biological function and global regulatory network of DegS in V. cholerae remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…The cAMP-CRP complex can bind to the promoter region of rpoS and further stimulate the transcription of this gene (Cheng & Sun, 2009). RpoS is an alternative sigma factor (σ S ) of RNA polymerase that plays a role in the general stress response and modulation of the stationary phase (Weber et al, 2005; Pennetzdorfer et al, 2019). In V. cholerae , rpoS mutants are highly sensitive to hydrogen peroxide and are involved in colonization during the infection process and in the dissolution of biofilms (Merrell et al, 2000; Müller et al, 2007).…”
Section: Discussionmentioning
confidence: 99%